Risk-taking as a contributing factor to make learning English a success - Ermyna Seri (Jurnal Linguistik Terapan, 2013)
The success of language learning can be affected by internal and external factors. One of the internal factors is risk-taking. This factor drives learners to be able to gamble a bit, to be willing to try out hunches about the language and take the risk of being wrong. This article elaborates the characteristics of risk-taking learners on learning English, the learners’ personal learning problems on learning English, and the methods of increasing risk-taking ability. The methods discussed here directly address the learners’ personal learning problems which include inhibition to speak, low self-esteem, lack of motivation, and low risk-taking ability. Considering the significant role of risk-taking to the success in learning English, language teachers should establish an encouraging class atmosphere or a nonthreatening classroom climate in their classes to reveal risk takers.